Simulation on the performance of ejector in a parallel hybrid ejector-based refrigerator-freezer cooling cycle. (1st July 2017) - Hou, Wenxiu; Wang, Lei; Yan, Jia; Li, Xianbi; Wang, Ling
Highlights: A parallel hybrid ejector-based refrigerator-freezer cooling cycle is established. Simulation is conducted to seek optimum ejector geometric parameters. An adjustable ejector with a spindle is proposed to meet variable cooling loads. The effect of blocking percentage of nozzle on ejector performance is investigated. The effect of back pressure on the adjustable ejector performance is identified. Abstract: In this paper, the simulation is carried out to investigate the performance of ejector used in a parallel hybrid ejector-based refrigerator-freezer cooling cycle. The geometric parameters such as primary nozzle diameter, area ratio and constant-pressure mixing chamber length are studied firstly to achieve a good performance of the fixed area ratio ejector under a certain condition. Based on the obtained ejector geometry, an adjustable ejector with a spindle is used in the system to meet the requirements of variable cooling loads. The results show that the effect of blocking percentage of primary nozzle with a spindle on the ejector performance is considerable. Moreover, the adjustable ejector works well with relatively high entrainment ratio when the back pressure increment percentage as compared to the secondary flow pressure is no less than 16.15%.